تقويم فاعلية نظام المعلومات الإدارية من وجهة نظر المستفيد - عامر إسماعيل حديد (PROSPECTIVE RESEARCHES, 2023)
This study aims at evaluating the Management Information System Effectiveness from the standpoint of the user's satisfaction. To achieve this goal, the researcher has adopted a survey study at the State Company for Drug Industries and medical appliances In Nineveh (N.D.I) , because it is one of the largest and most important companies in the province. The data of the study have been provided through questionnaire including questions that cover four hubs, each hub covers Index of the indicators the effectiveness measure agreed upon by the Writers. This questionary has been given to the users of the system in the company. The data of the study have been analyzing used, we used the descriptive statistical indicators, in addition to (ANOVA) Test. The analysis findings come to prove the hypotheses of the study and to come out with several conclusions, such as the direct correlation between the effectiveness system and achievement of the objectives of the organization, besides a number of recommendations that Focus on the importance of management information system for decision makers.